Association between estimated glucose disposal rate with the all-cause and cause-specific mortality among the population with cardiometabolic syndrome - Chao Fu; Yuxin Li; Xiangyang Gao; Yan Gong; Hantong Wang; Guanyun Wang; Xiaoxue Ma; Bingqing Han; Shanshan Liu; Hao Zhang; Fei Wang; Qiang Zeng (Diabetology & Metabolic Syndrome)
Abstract Background Estimated glucose disposal rate (eGDR) is considered as a reliable alternative indicator of insulin resistance. However, the relationship between eGDR levels and mortality among individuals with cardiometabolic syndrome (CMS), as well as within different glucose metabolic states in this population, remains unclear. Methods We conducted a cohort study on 9928 CMS participants from the National Health and Nutrition Examination Survey (NHANES) database from 1999 to 2018. The relationship between eGDR levels and mortality in the CMS population was evaluated using multivariable Cox proportional hazards regression models and restricted cubic splines (RCS). Finally, stratified analysis was performed to determine the relationship between eGDR levels and mortality in different subgroups. Results Cox regression analysis showed a significant correlation between eGDR levels and both all-cause and cause-specific mortality in the entire CMS population (all p < 0.05). RCS analysis revealed a non-linear relationship between eGDR levels and both all-cause (p for overall < 0.001, p for non-linear < 0.001) and diabetes specific mortality (p for overall < 0.001, p for non-linear = 0.004) in CMS population, while a linear relationship with cardiovascular specific mortality (p for overall < 0.001, p for non-linear = 0.091). In participants with baseline diabetes mellitus (DM), eGDR levels were significantly correlated with all-cause mortality, cardiovascular specific mortality, and diabetes specific mortality (all p < 0.05). In CMS participants with baseline pre-diabetes mellitus (Pre-DM), eGDR levels were significantly correlated with cardiovascular-specific and diabetes-specific mortality (all p < 0.05). In CMS participants with baseline normal glucose regulation (NGR), eGDR levels were only significantly related to diabetes specific mortality (p < 0.05). Conclusion There is a significant correlation between eGDR levels and both all-cause and cause-specific mortality in the entire CMS population. Furthermore, the protective effect of high eGDR levels on mortality persists across various glucose metabolic states.